Emotional Intelligence and Athletic Achievement: Comparing Table Tennis and Taekwondo Athletes - Septian Williyanto; Nurlan Kusmaedi; Herman Subarjah; Diftha Nusa Al fitra; Sri Wicahyani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Emotional intelligence (EI) is considered an important psychological factor in sports performance; however, its role may vary depending on sport characteristics and competitive demands. This study aimed to compare emotional intelligence between athletes in a non-contact sport (table tennis) and a contact sport (taekwondo), and to examine the association between emotional intelligence and athletic achievement. A quantitative comparative–correlational design was employed involving 95 athletes (49 table tennis; 46 taekwondo) from West Java, Indonesia. Emotional intelligence was measured using the Trait Meta-Mood Scale (TMMS-24), while athletic achievement was assessed through a structured scoring system based on official competition medals. Data were analyzed using descriptive statistics, independent samples t-tests, and correlation analyses. Descriptive results indicated that table tennis athletes had a higher mean EI score (M = 93.53, SD = 10.24) compared to taekwondo athletes (M = 88.73, SD = 15.23). However, the difference was not statistically significant (p = 0.076). Correlation analysis revealed a positive but weak association between emotional intelligence and athletic achievement (Pearson r = 0.285; Spearman ρ = 0.199). These findings suggest that emotional intelligence contributes to athletic performance as a supportive factor, but it is not a sole determinant of achievement. Athletic success is influenced by multiple interacting factors, including technical skills, physical condition, training experience, and competitive exposure. Therefore, athlete development programs should integrate psychological training alongside physical and technical preparation in a balanced and sport-specific manner.